Desarrollo de vidrios bioactivos para aplicaciones biológicas - Lanche Carrión, Karen Ivanova (2018)
Abstract:Bioactive glasses are biomaterials that act as implants, have the ability to repair and regenerate damaged bone.They bind to the bone forming a stable union between the them, called hydroxyapatite. To be aceptable, it may has Ca/P ratio of 1.67 similar to that present by the bone. The objective of this study is the production of bioactive glasses using the sol-gel technique. Bioactive glasses with the following composition were obtained: sample 1 (SiO2-NaO- CaO-P2O5), sample 2 (SiO2-NaO- CaO-P2O5), sample 3 (SiO2-NaO-CaO-P2O5-CuO) and sample 4 (SiO2-NaO-CaO-P2O5-Ag2O). To check their bioactivity they were immersed in phosphate buffer solution (PBS) for 7,14 and 21 days at 37°C, analyzed with x-ray diffraction (XRD) and x-ray fluorescence (FRX). In the x-ray diffraction analysis, it was observed that the samples presented an amorphous form, with crystalline phases for hydroxyapatite, copper and silver. In the x-ray fluorescence analysis, the samples showed a Ca/P ratio of 1.502 (sample 1), 1.912 (sample 2), 1.279 (sample 3) and 1.486 (sample 4)